Social Pragmatic Failure of Indonesian Mandarin Learners at Elementary Level - Dan Dan, Liu; I Made, Suastra; Septevany, Elvira (e-Journal of Linguistics; Vol 15 No 2 (2021): e-jl July, 2021)
The aim of this study is to help Indonesian learners avoid the failure of social pragmatics in intercultural communication and achieve successful communication goals. The data collection technique was carried out in two ways, the one way was done by distributing questionnaires given by google form, and the other way was done by direct observation when the author had daily conversations with Indonesian learners which were followed up with orthographic recording and note-taking techniques. The sampling technique was carried out by purposive sampling. The samples used were students at the elementary level learning Mandarin at Universitas Hasanuddin and Sekolah Islam Athirah of Indonesia. Through analyze, the results of the usage of Mandarin with a contextual approach, we find that there are 4 main types of social pragmatic failures committed by Indonesian learners at their elementary stage. These four types social pragmatic failures consist of failure to address people, failure to greeting, failure to farewell, and failure to ask for permission.